1999
DOI: 10.1159/000026618
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Plasma Levels and Immunological Changes during Academic Stress

Abstract: Academic stress is a good model of psychological stress in humans for studying psychoneuroimmune correlations. We looked for correlations between psychological scores, immune tests and plasma levels of cortisol and neuropeptide Y (NPY). A group of medical students were evaluated at the beginning of the academic year (Baseline) and the day before an examination (Stress). They underwent evaluation by The Profile of Mood States (POMS), The Malaise Inventory, The Self Efficacy Scale and A Global Assessment of Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
1
15
0
3
Order By: Relevance
“…Plasma NPY concentrations, on the other hand, did not show any correlation with serum cortisol concentrations. This finding is consistent with the dissociation between cortisol and NPY under various stresses (34,35), and the finding that adrenalectomy revealed no effect on plasma NPY concentrations (36). As to orexin-A, no direct correlation was found with cortisol concentrations in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma NPY concentrations, on the other hand, did not show any correlation with serum cortisol concentrations. This finding is consistent with the dissociation between cortisol and NPY under various stresses (34,35), and the finding that adrenalectomy revealed no effect on plasma NPY concentrations (36). As to orexin-A, no direct correlation was found with cortisol concentrations in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Fourthly, the effect of stress on cytokine production should be considered. Both psychogenic and physiological stresses elicit proinflammatory processes in the CNS [69][70][71][72] . Because the patients were all hospitalized for a full 6 weeks, the changes in proinflammatory cytokines may be associated only with the acute psychotic state.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study was limited by its cross-sectional nature and the lack of cortisol data. To our knowledge, while others have shown that academic stress is associated with elevations in cortisol (Guidi et al 1999), no longitudinal human in vivo studies have shown that chronically elevated psychological stress, such as that experienced during academic exams, and elevated in vivo cortisol levels are associated with significant decrements in peripheral blood B lymphocytes.…”
Section: Introductionmentioning
confidence: 89%